Bravery And Resilience In Pittacus Lore's I Am Number Four Novel (2010): An Individual Psychological Approach - Fitriawati, Yunita, Dr.Phil. Dewi Candraningrum, Titis Setyabudi,S.S,.M..Hum (2013)
The major problem of this study is how bravery and resilience are reflected in Pittacus Lore‟s I Am Number Four novel. The objective of this study is to analyze the novel based on its structural elements and to analyze the novel based on individual psychological approach as major theory and bravery and resilience as issue. In analyzing I Am Number Four novel, the writer uses qualitative method and individual psychological approach. The data sources consist of primary data and secondary data sources. The primary data source is the novel I Am Number Four itself and the secondary data sources are the other sources related to the analysis such as the author‟s biography, books of literary theory of the object and issue. The method of the data collection is descriptive analysis. The result of the study shows the following conclusions. First, based on the structural analysis it is clear that in I Am Number Four novel, Pittacus Lore delivers message that bravery and resilience are needed in everyone‟s life because they are important and can influence someone‟s life to survive in their environment, because someone who has a strength, bravery and resilience can show who really they are and show their existance. Second, based on the individual psychological approach, it shows that bravery and resilience can give effect to people‟s mind